Theory into practice Composition, Performance and the Listening Experience - Cook, Nicholas (Collected Writings of the Orpheus Institute, 2021)
"Theory into Practice. Composition, Performance and the Listening Experience' is the second publication in the series 'Collected Writings of the Orpheus Institute'. The series comprises articles concerning the activities of the Orpheus Institute. The centrale theme of this book is the relationship between the reflections about and the relization of a musical composition. In his paper Words about Music, or Analysis versus Performance, Nicholas Cook states that words and music can never be aligned exactly with one another. He embarks on a quest for models of the relationship between analytical conception and performance that are more challenging than those in general currency. Peter Johnson's article Performance and the Listening Experience: Bach's 'Erbarme dich' shows that a performance is an element within the intentionality of the work itself. He looks for scientific methods capable of proving the artisticity of a performance. The composer Hans Zender, in his A Road Map for Orpheus?, states that a composer must be capable of questioning obvious basic principles (such as equal temperament) and finding creative solutions."